The Airborne Mycobiota of a Dust Storm in Comparison with a Calm Climate in Erbil City-Iraq - Saleem, Salah Mahdi; Zefenkey, Zean (Science Journal of University of Zakho, 2023)
A series of dust storms stroked Iraq from April to May 2022. These abnormal environmental events hold and transfer microorganisms far from their original sites. Mycobiome is a main part of the aerobiological aerosol, it includes agents of respiratory harm, opportunistic mycosis, as well as mycotoxin producers. 32 Petri dishes were exposed to the falling down dust for two days (S1). The time of exposure was 10 minutes per hour, a total of 8 samples/ day since 9:00 am. Sabouraud’s dextrose agar and pollen grains agar media were used. Sampling was identically repeated after two days during a calm climate (S2). Fungal genera, frequency%, and total similarity% were calculated for S1 and S2 samples.257 colonies (143CFU/m3) occurred in (S1) samples, in contrast, a total of 110 colonies from (S2) samples (59CFU/m3). The statistical analysis showed a highly significant difference between CFU for S1and S2 (p≤0.0001). Fifteen isolates were identified from (S1), and (5) from (S2). The highest occurrence O% and frequency F%  genera in S1   were, Aspergillus (65-6%; 15.9%), Alternaria (56.6%;11.2%), Cladosporium (46.8%; 13.6%), Penicillium(37.5%;8.1%), besides sterile mycelia, while in S2 were (40.6%; 30.6%) ; (25.0%; 17.2%); (32.0%; 26.3%) (34.3 %; 12.7%) respectively. The similarity between the fungal communities of the two times was low =35.7%.Results showed that air mycobiota on stormy days have a higher fungal abundance and diversity. All isolated fungi are adverse to humans, and animals.  Individuals who have respiratory problems or with weak immunity showed careful to protect themselves.
Keywords: airborne fungi; outdoor; Storm; Dust; air mycobiome; Iraq